Effect of Pore Size and Film Thickness on Gold-Coated Nanoporous Anodic Aluminum Oxide Substrates for Surface-Enhanced Raman Scattering Sensor - Kassu, Aschalew; Farley, Carlton; Sharma, Anup; Kim, Wonkyu; Guo, Junpeng (Sensors (Basel, Switzerland), 2015)
A sensitive surface enhanced Raman scattering chemical sensor is demonstrated by using inexpensive gold-coated nanoporous anodic aluminum oxide substrates. To optimize the performance of the substrates for sensing by the Surface-enhanced Raman scattering (SERS) technique, the size of the nanopores is varied from 18 nm to 150 nm and the gold film thickness is varied from 30 nm to 120 nm. The sensitivity of gold-coated nanoporous surface enhanced Raman scattering sensor is characterized by detecting low concentrations of Rhodamine 6G laser dye molecules. The morphology of the SERS substrates is characterized by atomic force microscopy. Optical properties of the nanoporous SERS substrates including transmittance, reflectance, and absorbance are also investigated. Relative signal enhancement is plotted for a range of substrate parameters and a detection limit of 10−6 M is established.